Bibliometric analysis on the evolution of knowledge structure of consumer behavior analysis in Telecommunications Policy - Jeesun Oh; Jeeeun Kim (International Telecommunications Society (ITS), 2018)
This paper aim to conduct a bibliometric analysis on the evolution of knowledge structure of empirical analysis of consumer behaviour in Telecommunications Policy. The related studies on the Telecommunications Policy, the academic journal specialized in communication industry and service research, have been conducted relatively recently to review the last 40 years. No research has been conducted on a specific topic including consumer behaviour in the journal. The research results are as follows. First, empirical analysis on consumer behavior has been growing quantitatively, but the article concentration on the 10 sample countries has also strengthened in the journal for the last 10 years. Second, there were differences in research themes and methods by periods and countries. Third, the number of citations in the empirical analysis was relatively higher than that of the all articles, but the citations were commonly concentrated in the top 10 countries. Finally, in the "Telecommunications Policy," the citation rate of empirical analysis paper is high. The "Telecommunications Policy" is cited the most because "Telecommunications Policy" has a long history and the journal covering multidisciplinary and international subject in the economy and society related ICT.
Keywords: 330; Bibliometric analysis; Knowledge structure; Empirical analysis; consumer behavior